The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.electacta.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of nitrogen heterocycles using environmentally friendly methodologies

Abstract: Cyclic voltammetry and constantcurrent electrolysis in a one-compartment cell with a sacrificial anode has been used to study the indirect electroreduction of N-allyl-haloamides by electrogenerated Ni(I) complexes conducted in N,N-dimethylformamide (DMF) and acetonitrile (ACN) and the results were compared with those obtained in protic solvents such as EtOH and EtOHH 2 O mixtures. It was observed that the indirect electrochemical reduction of N-allyl--haloamides led to the corresponding lactams and the yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Electrogenerated nickel(I) cyclam and nickel(I) tetramethyl cyclam have been employed to carry out a variety of reductive cyclization reactions involving allyl 2-halophenyl ethers, 177 propargyl and allyl bromoesters, 178−181 and N-allyl-α-haloamides. 182 Espenson and co-workers used these catalysts to reduce alkyl halides 183 and some α,ω-dihaloalkanes. 184,185 With this same class of catalysts, Ozaki et al accomplished a number of interesting electrosyntheses: (a) intramolecular cyclization of nallylic and n-propargylic α-bromoamides and of o-bromoacryloylanilides to give five-membered lactams; 186 (b) stereoselective addition of n-, sec-, and tert-butyl radicals to αmethylenebutyrolactones; 187 Electrogenerated nickel(I) tetrapyrrole complexes have been shown to catalyze the reductions of dichloromethane and methyl iodide, 193 alkyl halides, 194 and aryl halides.…”
Section: Indirect or Catalytic Cleavage Of Carbon−halogen Bondsmentioning
confidence: 99%
“…Electrogenerated nickel(I) cyclam and nickel(I) tetramethyl cyclam have been employed to carry out a variety of reductive cyclization reactions involving allyl 2-halophenyl ethers, 177 propargyl and allyl bromoesters, 178−181 and N-allyl-α-haloamides. 182 Espenson and co-workers used these catalysts to reduce alkyl halides 183 and some α,ω-dihaloalkanes. 184,185 With this same class of catalysts, Ozaki et al accomplished a number of interesting electrosyntheses: (a) intramolecular cyclization of nallylic and n-propargylic α-bromoamides and of o-bromoacryloylanilides to give five-membered lactams; 186 (b) stereoselective addition of n-, sec-, and tert-butyl radicals to αmethylenebutyrolactones; 187 Electrogenerated nickel(I) tetrapyrrole complexes have been shown to catalyze the reductions of dichloromethane and methyl iodide, 193 alkyl halides, 194 and aryl halides.…”
Section: Indirect or Catalytic Cleavage Of Carbon−halogen Bondsmentioning
confidence: 99%
“…Electroreduction of organic halides or related substrates, ketones, aromatic imines, cyclic imides, can generate carbon-centered radicals, which could be trapped by internal π-bond systems that tethered a heteroatom leading to the formation of heterocycles.…”
Section: Intramolecular Cyclizationmentioning
confidence: 99%
“…In 2009, Medeiros and co-workers found that Ni­(tmc)­Br 2 was also an effective catalyst for electroreductive cyclization of N -allyl-α-haloamides (Scheme ). When N -allyl- N -methyl-2-bromoethanamide 50 was employed as a substrate, cyclic product 51 was furnished in 18% yield; cyclized products 53 and 54 were obtained in 53% total yield from the electroreductive cyclization of 52 . These reactions were accomplished in a single-compartment cell equipped with a sacrificial magnesium anode and a carbon fiber cathode using n- Bu 4 NBF 4 as the supporting electrolyte.…”
Section: Intramolecular Cyclizationmentioning
confidence: 99%
“…Later, Medeiros and co‐workers obtained better results in terms of yields and selectivities by conducting the electrosyntheses in “green” solvents such as EtOH and EtOH‐H 2 O mixtures …”
Section: Intramolecular α‐Alkylation Of α‐Haloamides: Syntheses Of γ‐mentioning
confidence: 99%